Special topics in education, volume one - Baylongo, Joselina T.; Cuartel, Imelda E.; Carren, Myrnz; Iringan, Tomasa C.; Castro, Flordeliza A.; Salazar, Cecilia G.; Borabo, Milagros L..; Prieto, Nelia G.; Lucido, Paz I.; Ayunon, Bernardita C. (Cubao, Quezon City : Lorimar Publishing, 2012)
These modules on Special Topic in Education are PAFTE's response to the need for instructional material for the three-unit professional education course in Special Topics. It is a compilation of at least ten (10) Modules written by members of PAFTE all over the country for PAFTE members most especially and also for non- PAFTE members. The teacher education curriculum includes a three-unit course on Special Topics to give every teacher education institution an opportunity to select current issues and topics not included in the other professional education courses but are seen to be important and highly relevant to its mission vision. The course on Special Topic likewise gives the teacher education student an opportunity to explore topics and issues related to his/ her field of study.
On Becoming a Transformational Leader: What is and What Not? / Joselina T. Baylongo 1 -- How Do You Effectively Engage Your Students in Learning? / Imelda E. Cuartel 9 -- Safeguarding the Environment our Earth, our Home (Let's Go Green / Myrna L. Carreon 24 -- Becoming An Exemplary Instructional Leader / Tomasa C. Iringan 35 -- Journeying the Teaching Profession:= Myself and My Career/ Flordeliza A. Castro 51 -- Are Men Different from Women/ Cecelia G. Salazar 62 -- What Skills Do You Need for the 21st Century? Are You Ready? / Milagros L. Borabo 70 -- Effective Instructional Strategies in Inclusive Education/ Nelia G. Prieto 78 -- Teaching New Literacy in a Digital Environment/ Paz I. Lucido 88 -- Are You Creative and Imaginative/ Bernadita C. Ayunon 94
Includes bibliographical references.
Keywords: EDUCATION -- PHILIPPINES